An analysis on the applicability of risk based internal auditing: a case of Crowne Plaza Monomotapa hotel - Marufu, Primrose R. (Midlands State University, 2014)
This study sought to analyse the applicability of risk based internal auditing in Crowne Plaza Monomotapa Hotel. The literature from different authors was reviewed concerning the research topic. The main goal of this research was to analyse if risk based internal auditing can be applied in the hotel, how can it be implemented and is there adequate staff and resources for it to be implemented. The researcher used a descriptive design as a research design. The researcher used stratified random sampling to determine the population and the sample size. Questionnaires and interviews were the research instruments used to gather data for the research. A sample size of 20 respondents was used in carrying out the research study; the management, internal auditors and staff of the hotel were included in the sample. The data was collected and analysed using tables, graphs and pie charts. Basing on the research Crowne Plaza Monomotapa Hotel cannot implement risk based internal auditing since there is no risk management framework though the hotel has other necessary resources. The research recommended that the organization board should devise a strategy that will establish the a risk management framework which will enable he hotel to implement risk based internal auditing that can mitigate the risks being faced by the hotel.